Contextualizing civilized character in ELT: Philosophical approach - Aminah Aminah (Institut Parahikma Indonesia, 2020)
Every knowledge in this life must be under the philosophy scope including education. Moreover, education is not only a matter of transferring knowledge from a teacher to the students but also a matter of educating them to have good character. Some educators ignore it due to the materialistic or hedonism perspective which is dominant in dealing with their job performances. As a result, character value seems to be neglected. Moreover, moral education is discussed in several terms namely character building, character value and, in this article, it is called civilized character. In term of instilling or contextualization of civilized character depends on the quality and awareness of the teacher. Teacher professional development is the key before realizing it and applying it to be a good pattern for the student. Hence, enriching teachers’ quality in cognitive and soft skill is urgent. In ELT, the integration of technology, general knowledge, and religious studies are broken down into learning activities. Similarly, the integration is assimilated with the students learning styles (kinesthetic, audio, and visual). Thus, the assessment aspect also should consider civilized character, affective, psychomotor, instead of focusing on cognitive only. It is expected that teacher contribution is in line with the civilized character internalized during teaching and learning process and will be inherent in daily life since philosophically all of us are the lifelong learners who face the real faculty of education.